Compositional and toxicological investigation of pooled venom from farm-raised Naja atra - Xiao,Gang (2022)
Abstract Background: Naja atra is a venomous snake species medically relevant in China. In the current study, we evaluated the composition and toxicological profile of venom collected from farm-raised N. atra. Methods: Venom was collected from third-generation captive bred N. atra on a snake farm in Hunan Province, China. The venom was analyzed using sodium dodecyl sulfate polyacrylamide gel electrophoresis and nano-liquid chromatography with electrospray ionization tandem mass spectrometry. In addition, hemolytic activity, median lethal dose, serum biochemical and histopathological parameters were accessed. Results: N. atra venom proteome was dominated by phospholipase A2 (46.5%) and three-finger toxins (41.4 %), and a set of common low relative abundance proteins, including cysteine-rich secretory proteins (4.7%), NGF-beta (2.4%), snake venom metalloproteinase (1.5%), glutathione peroxidase (0.6%), vespryn (0.3%), and 5ʹ-nucleotidases (0.2%) were also found. Furthermore, the venom exhibited direct hemolytic activity, neurotoxicity, myotoxicity, and high lethal potency in mice, with a subcutaneous median lethal dose of 1.02 mg/kg. Histopathological analysis and serum biochemical tests revealed that venom caused acute hepatic, pulmonary and renal injury in mice. Conclusion: This study revealed the composition and toxicity of venom collected from farm-raised N. atra, thereby providing a reference for the analysis of venom samples collected from captive-born venomous snakes in the future.